Study guide for essentials of anatomy and physiology - Case, Drew (St. Louis, Missouri : Elsevier Mosby, 2012)
e all-new Study Guide for Essentials of Anatomy & Physiology offers valuable insights and guidance that will help you quickly master anatomy and physiology. This study guide features detailed advice on achieving good grades, getting the most out of the textbook, and using visual memory as a learning tool. It also contains learning objectives, unique study tips, and approximately 4,000 study questions with an answer key - all the tools to help you arrive at a complete understanding of human anatomy.
Chapter 1 Organization of the human body -- Chapter 2 The chemistry of life -- Chapter 3 Anatomy of cells -- Chapter 4 Physiology of cells -- Chapter 5 Cell growth and reproduction -- Chapter 6 Tissues and their functions -- Chapter 7 Skin and its appendages -- Chapter 8 Skeletal tissues -- Chapter 9 Bones and joints -- Chapter 10 Muscular system -- Chapter 11 Cells of the nervous system -- Chapter 12 Central nervous system -- Chapter 13 Peripheral nervous system -- Chapter 14 Sense organs -- Chapter 15 Endocrine system -- Chapter 16 Blood -- Chapter 17 Anatomy of the cardiovascular system -- Chapter 18 Physiology of the cardiovascular system -- Chapter 19 Lymphatic and immune systems -- Chapter 20 Respiratory system -- Chapter 21 Digestive system -- Chapter 22 Nutrition and metabolism -- Chapter 23 Urinary system and fluid balance -- Chapter 24 Male reproductive system -- Chapter 25 Female reproductive system -- Chapter 26 Growth and development -- Chapter 27 Human genetics and heredity.
Keywords: HUMAN ANATOMY -- PROBLEMS, EXERCISES, ETC